Financial Literacy and Retirement Preparedness among Generation Y Employees: A Case Study of Maybank Branches in Klang Valley, Malaysia - Kee, Sook Sim (2025)
This study explores the relationship between financial literacy and retirement preparedness among Generation Y employees, with a specific focus on Maybank branches in Klang Valley, Malaysia. It addresses a significant gap in understanding how demographic factors, such as age, gender, marital status, education, and financial literacy—impact retirement planning behaviors within this cohort. Grounded in the Theory of Planned Behavior (TPB) and the Life-Cycle Hypothesis (LCH), the research aims to develop a comprehensive framework for analyzing the determinants of retirement preparedness in a dynamic financial environment. Data were collected from 357 employees using a quantitative approach, and Pearson correlation analysis was used to examine the relationships between the independent variables and retirement preparedness. The findings reveal valuable insights: while age and gender were expected to influence retirement preparedness, no significant linear relationship was observed between these factors. In contrast, marital status showed a modest but significant negative correlation, indicating that certain marital statuses face unique challenges in retirement planning. Furthermore, strong positive correlations were identified between both higher educational attainment and financial literacy with retirement preparedness, underscoring the critical role of education and financial knowledge in shaping retirement outcomes. Most notably, financial literacy emerged as a key factor, demonstrating a strong positive relationship with retirement preparedness, emphasizing the importance of financial education in enabling informed retirement decisions. The study contributes to the theoretical discourse by integrating TPB and LCH, offering a strong framework for understanding how attitudes, social norms, and perceived behavioral control influence retirement planning. Practical implications highlight the need for targeted financial education programs within Malaysia’s banking sector to enhance long-term financial security for Generation Y employees.